1) 2√7 * х + √28 * х - 3√700 * х = 2√7 * х + √(4 * 7) * х - 3√(100 * 7) * х = 2√7 * х + 2√7 * х - 3 * 10√7 * х = 4√7 * х - 30√7 * х = - 26√7 * х.2) (3 - √2) * (5 + √8) = 3 * 5 + 3 * √8 + (- √2) * 5 + (- √2) * √8 = 15 + 3 * √(4 * 2) - 5√2 - √(2 * 8) = 15 + 3 * 2√2 - 5√2 - √16 = 15 + 6√2 - 5√2 - 4 = 11 + √2.3) (2 + √15) * (√5 - √3) = 2 * √5 + 2 * (- √3) + √15 * √5 + √15 * (- √3) = 2√5 - 2√3 + √(5 * 3) * √5 - √(5 * 3) * √3 = 2√5 - 2√3 + √5 * √3 * √5 - √5 * √3 * √3 = 2√5 - 2√3 + (√5)² * √3 - √5 * (√3)² = 2√5 - 2√3 + 5√3 - 3√5 = 3√3 - √5.